INFLUENCE OF TOTAL NECK LENGTH AND ANTEROPOSTERIOR DIAMETER OF THE HEAD ON TOTAL HEAD EXCURSION - A PROSPECTIVE STUDY - Baroor, Vrindha; Raj, Gayathri; Raj, Michael; Lamba, Dheeraj (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: It is estimated that a third of all adults will experience neck pain throughout the course of 1 year, and 70% is the approximate lifetime prevalence. Neck pain is most commonly reported musculoskeletal pain site in population surveys and primary care. Neck pain can be periodic and can vary in disability. It is important that health-care professionals provide straightforward, clear advice on supervision at an early stage. The purpose of the study was to find variation of total neck length and anteroposterior (AP) diameter of head on total head excursion (THE) which would result in high-risk factor. Methods: 600 individuals both males and females 8-60 years of age were assigned according to inclusion criteria into three groups and measurement was done through metric ruler scale. Neck length was measured using digital vernier caliper, and AP diameter of the head was measured using spreading caliper. Results: ANOVA and independent t-test show no significant difference between neck length and AP diameter of head on THE. However, Pearson sig 2-tailed shows a positive correlation with neck length and AP diameter of head on THE. Conclusion: The findings of the present study states as AP diameter of head decreases, there is decrease in neck length and decrease in retraction and increase in protraction or if there is increase in AP diameter and increase in neck length, there is increase in retraction and decrease in protraction. Â 